Effect of Age and Breed on Carcass and Meat Quality Characteristics of Beni-Guil and Ouled-Djellal Sheep Breeds - Kamal Belhaj; Farid Mansouri; Aziz Tikent; Yassin Taaifi; Mohamed Boukharta; Hana Caid Serghini; Ahmed Elamrani (The Scientific World Journal)
Two hundred eight sheep, belonging to two main breeds of eastern Morocco, “Beni-Guil” and “Ouled-Djellal,” were investigated for carcass traits and meat quality. The objective of this study is to determine the effects of breed and age at slaughter on carcass traits and meat quality. The animals were slaughtered at three age classes: milk teeth, animals with two adult teeth, and adult animals. Dressing percentage, carcass measurements, compactness indices, carcass shrinkage parameter, conformation scores, fatness state, fat consistency, fat and meat colour, and pH were measured 24 hours postmortem. The results showed that the dressing percentage, carcass measurements, and compactness indices increased with slaughter age (p<0.001). Furthermore, the effect of breed was higher for Ouled-Djellal breed of carcass characteristics (p<0.01). However, no significant effect was observed for carcass shrinkage parameter. The longissimus lumborum muscle was used to determine the meat colour, which ranged from 23.89 to 21.96, while the ultimate pH ranged from 5.70 to 5.82. These results were influenced by age at slaughter (p<0.05) but not influenced by breed. Breed and age at slaughter had a significant influence on carcass traits (p<0.001). The present study provided a new insight into the effect of breed and age at slaughter on carcass and meat traits of both “Beni-Guil-PGI” and Ouled-Djellal sheep breeds.